Remote Control Android-based Applications for a Home Automation implemented with Arduino Mega 2560 and ESP 32 - Susany, Robert; Rotar, Raul (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
As technology becomes cheaper and more reliable, people are taking advantage of it to improve their standard of living. This paper describes how we can integrate some of the available technology into our daily lives to create a safe and comfortable living environment. The provision of high-speed Internet makes it easy to access and monitor various types of devices in real-time from a desktop, a tablet or any device that has the capability to do so. With the help of this framework, all smart home sensors and devices can be tailored to the user's personal needs, and some of the parameters can even be observed and controlled using a mobile phone. There are a range of home automation systems on the market, but they are either generic or, if customizable, costly. The goal of this project was to develop secure and affordable home applications and to examine how some of the applications can be operated from very large distances using Wi-Fi and smartphone technology.